Penerapan Expressive Writing Therapy terhadap Penurunan Gejala pada Pasien Harga Diri Rendah dan Halusinasi - Erina Adriana Paramitha; Wita Oktaviana; Pudji Lestari (Journal of Telenursing (JOTING), 2026)
This study aimed to determine the effectiveness of Expressive Writing Therapy in reducing symptoms in patients with low self-esteem and auditory hallucinations. This study used a quantitative method with a pre-experimental one-group pretest-posttest design. The results showed a significant increase in hallucination control scores (from 13.0 to 21.4; p=0.043) and self-esteem scores (from 13.0 to 22.2; p=0.042). In conclusion, expressive writing therapy is effective as a psychiatric nursing intervention to help patients recognize, control, and redirect responses to hallucinations and promote a more positive self-perception.   Keywords: Auditory Hallucinations, Low Self-Esteem, Expressive Writing Therapy